Corrigendum to: Interactions between the introduced European honey bee and native bees in urban areas varies by year, habitat type and native bee guild - Prendergast, Kit; Dixon, Kingsley; Bateman, Bill (2021)
This paper was published in the July 2021 issue, Vol. 133, No. 3, pp. 725-743. In the originally published version of this manuscript, Figures 1C and 1D needed to have their labels switched. There were also errors in the paragraph that read: In the first year, honey bee abundance had a significant positive relationship with native bee species richness (estimate: 0.14; R2 = 0.19; P < 0.001; Fig. 1B). There was also a significant interaction with habitat (P = 0.01). Although the relationship remained significant and positive in both bushland remnants and residential gardens, the association was stronger in residential gardens (estimate: 0.22; R2 = 0.43, P < 0.001) compared with bushland remnants (estimate: 0.08; R2 = 0.16, P = 0.05; Fig. 1C). In contrast, in the second year, there was a significant negative, albeit weak, relationship between native bee species richness and honey bee abundance (estimate: −0.06; R2 = 0.05, P = 0.01; Fig. 1D). There was no interaction with habitat type (P = 0.95). Model outputs for the interaction variables and the relationship between honey bee abundance and native bee abundance and species richness can be found in Supporting Information 1 (Tables S2 and S3, respectively). This should have read: In the first year, honey bee abundance had a significant positive relationship with native bee species richness (estimate: 0.14; R2 = 0.19; P < 0.001) (Fig. 1B). There was also a significant interaction with habitat (P = 0.01). Although the relationship remained significant and positive in both bushland remnants and residential gardens, the association was stronger in residential gardens (estimate: 0.22; R2 = 0.43, P < 0.001) compared with bushland remnants (estimate: 0.08; R2 = 0.16, P = 0.05) (Fig. 1B). In contrast, in the second year, there was a significant negative, albeit weak, relationship between native bee species richness and honey bee abundance (estimate: −0.06; R2 = 0.05, P = 0.01) (Fig. 1D). There was no interaction with habitat type (P = 0.95). Model outputs for the interaction variables and the relationship between honey bee abundance and native bee abundance and species richness can be found in Supporting Information 1 (Table S2 and S3 respectively). These errors have now been corrected online.